Intradermal Immunization of EBOV VLPs in Guinea Pigs Induces Broader Antibody Responses Against GP Than Intramuscular Injection - Liu, Ying; Wen, Zhiyuan; Carrion, Ricardo; Nunneley, Jerritt; Staples, Hilary; Ticer, Anysha; Patterson, Jean L.; Compans, Richard W.; Ye, Ling; Yang, Chinglai (Frontiers in microbiology, 2020)
Ebolavirus (EBOV) infection in humans causes severe hemorrhagic fevers with high mortality rates that range from 30 to 80% as shown in different outbreaks. Thus the development of safe and efficacious EBOV vaccines remains an important goal for biomedical research. We have shown in early studies that immunization with insect cell-produced EBOV virus-like particles (VLPs) is able to induce protect vaccinated mice against lethal EBOV challenge. In the present study, we investigated immune responses induced by Ebola VLPs via two different routes, intramuscular and intradermal immunizations, in guinea pigs. Analyses of antibody responses revealed that similar levels of total IgG antibodies against the EBOV glycoprotein (GP) were induced by the two different immunization methods. However, further characterization showed that the EBOV GP-specific antibodies induced by intramuscular immunization were mainly of the IgG2 subtype whereas both IgG1 and IgG2 antibodies against EBOV GP were induced by intradermal immunization. In contrast, antibody responses against the EBOV matrix protein VP40 induced by intramuscular or intradermal immunizations exhibited similar IgG1 and IgG2 profiles. More interestingly, we found that the sites that the IgG1 antibodies induced by intradermal immunizations bind to in GP are different from those that bind to the IgG2 antibodies induced by intramuscular immunization. Further analyses revealed that sera from all vaccinated guinea pigs exhibited neutralizing activity against Ebola GP-mediated HIV pseudovirion infection at high levels. Moreover, all EBOV VLP-vaccinated guinea pigs survived the challenge by a high dose (1000 pfu) of guinea pig-adapted EBOV, while all control guinea pigs immunized with irrelevant VLPs succumbed to the challenge. The induction of both IgG1 and IgG2 antibody responses that recognized broader sites in GP by intradermal immunization of EBOV VLPs indicates that this approach may represent a more advantageous route of vaccination against virus infection.